Surgical Outcome of Endoscopic Transsphenoidal Surgery for Giant Pituitary Adenoma - Abdulrahman Alrefaey Aldengawy; Ahmed Mohamed Taha; Mostafa Alsayed Mohamed (International Journal of Medical Arts, 2021)
Background: Pituitary adenomas are benign neoplasms representing 10 to 15% of intracranial lesions. Giant pituitary adenomas describe tumors more than 4 cm in maximum diameter and represent 6-10% of pituitary tumors. The introduction oftruly ‘extended endonasal’ approaches has enabled thepituitary surgeon to achieve a more radical resection safely. The aim of the work: Evaluation of efficacy of the endoscopic endonasal approach in managing giant pituitary adenoma. Patients and methods: Fifteenpatients with giant pituitary adenomas were enrolled. They were submitted to full clinical examination, radiological, visual, and hormonal assessment in the pre and postoperative period. A purely endoscopic endonasal approach was used as the primary surgical management for all the patients. The collected data included preoperative data, tumor characteristics, resection rate, clinical outcome, recurrence rate, and need for adjuvant radiotherapy Results: The mean age was 40.7 [range 16-57] years, with a male predominance [60%]. Visual affection was reported in [86.6%] with pituitary hormonal hypersecretion in 53.3%. There was an improvement in 80% of patients with visual field defects and 83.3% of patients with diminished visual acuity. Prolactin hormone levels normalized in 40%, while growth hormone normalized in 33.3%. Follow-up MRI revealed gross total resection [GTR] in 41.6% of patients with suprasellar extension, subtotal removal [about 80% of the tumor] in 50% of patients, partial tumor resection in one patient [8.4%].  In para-sellar extension, subtotal resection achieved [in 66.6%], and partial resection in 33.3%. Postoperative CSF leak occurred in 13.3% due to uncomplete reconstruction of the sella. They were reoperated for sella repair and augmentation. Three patients [20%] had transient [for 3 weeks] postoperative diabetes insipidus [DI] in the early postoperative period. Conclusion: Endoscopic endonasal approach is an effective and safe approach for managing giant pituitary adenomas.